Studi Literatur: Pengaruh Lingkungan Sekolah Terhadap Minat Belajar Peserta Didik Mata Pelajaran Biologi - Limbong, Forentina; Naura Kamila Manik , Aryediatami; Arwita, Widya; Hasruddin, Hasruddin; Djulia, Ely (JURNAL BIOSHELL, 2025)
Education fosters students' curiosity and enthusiasm for learning. As a psychological aspect, interest in learning plays an important role by evoking a sense of enjoyment and comfort in learning without external pressure. This study focuses on the influence of school environment conditions on students' interest in learning, including factors such as physical facilities, classroom atmosphere, teacher-student interaction, and parental support. The research method used was a literature review, involving a collection of relevant studies from PubMed and Google Scholar published between 2021 and 2023, using the keywords "learning interest" and "school environment".These findings reveal that the school environment significantly contributes to increasing interest in learning. Adequate facilities, a supportive classroom atmosphere, and positive teacher-student relationships effectively encourage greater interest in learning.